(untitled) (Annals of African Medical Research, 2018)
Acute urinary retention is a urological emergency presenting with a sudden inability to pass urine due to mechanical or functional reason characterized by suprapubic pain and distension requiring urgent bladder drainage. Acute urinary retention is ten times more common in males than females. Female genital mutilation comprises all surgical procedures involving partial or total removal of the female external genitalia or other injuries to the female genital organ for cultural and other non-therapeutic reasons. We present an 11 year old girl who was referred from a primary health centre with recurrent history of acute urinary retention following a female genital mutilation done 5 days prior to presentation, she was said to have been having suprapubic tapping of the urine to relive her of the retention as the health providers were unable to identify the urethral orifice for catheterization. On examination; she was in painful distress with complain of suprapubic pain and urge to pass urine, there is tender suprapubic distention, the left upper labia majora, minora and clitoris were severed, the urethral meatus distorted. Examination under anaesthesia with suprapubic cystostomy and urethral catheterisation was done and the patient was placed on sitz bath and genital toileting. We report a case of acute urinary retention in an 11 year old girl following a female genital mutilation five days earlier.